The day/night difference in the circadian clock's response to acute lipopolysaccharide and the rhythmic Stat3 expression in the rat suprachiasmatic nucleus - Moravcová, Simona; Pačesová, Dominika; Melkes, Barbora; Kyclerová, Hana; Spišská, Veronika; Novotný, Jiří; Bendová, Zdenka (PLoS One, 2018)
The circadian clock in the suprachiasmatic nucleus (SCN) regulates daily rhythms in physiology and behaviour and is an important part of the mammalian homeostatic system. Previously, we have shown that systemic inflammatory stimulation with lipopolysaccharide (LPS) induced the daytime-dependent phosphorylation of STAT3 in the SCN. Here, we demonstrate the LPS-induced Stat3 mRNA expression in the SCN and show also the circadian rhythm in Stat3 expression in the SCN, with high levels during the day. Moreover, we examined the effects of LPS (1mg/kg), applied either during the day or the night, on the rhythm in locomotor activity of male Wistar rats. We observed that recovery of normal locomotor activity patterns took longer when the animals were injected during the night. The clock genes Per1, Per2 and Nr1d1, and phosphorylation of kinases ERK1/2 and GSK3β are sensitive to external cues and function as the molecular entry for external signals into the circadian clockwork. We also studied the immediate changes in these clock genes expressions and the phosphorylation of ERK1/2 and GSK3β in the suprachiasmatic nucleus in response to daytime or night-time inflammatory stimulation. We revealed mild and transient changes with respect to the controls. Our data stress the role of STAT3 in the circadian clock response to the LPS and provide further evidence of the interaction between the circadian clock and immune system.
Keywords: Suprachiasmatic Nucleus; cirkadiánní rytmus; STAT3 Transcription Factor; MAP kinasový signální systém; mužské pohlaví; krysa rodu Rattus; Locomotion; Male; Mitogen-Activated Protein Kinase 3; regulace genové exprese; Rats; Lipopolysaccharides; nucleus suprachiasmaticus; potkani Wistar; lokomoce; Animals; lipopolysacharidy; transkripční faktor STAT3; zvířata; Circadian Rhythm; Rats, Wistar; mitogenem aktivovaná proteinkinasa 3; MAP Kinase Signaling System; Gene Expression Regulation